Book review: Academic libraries and collaborative research services - Eklund, Pieta (Information Research an international electronic journal, 2023)
Forbes, C. (ed.). Academic libraries and collaborative research services. London: Rowman & Littlefield, 2022. xiv, 298 p. ISBN 978-1-5381-5369-7